High-quality AlGaN epitaxy on lattice-engineerable AlN template for high-power UVC light-emitting diodes. (March 2022) - Walde, Sebastian; Huang, Cheng-Yao; Tsai, Chia-Lung; Hsieh, Wen-Hsuang; Fu, Yi-Keng; Hagedorn, Sylvia; Yen, Hung-Wei; Lu, Tien-Chang; Weyers, Markus; Huang, Chia-Yen
Abstract: AlGaN-based UVC light-emitting diodes (LED) were fabricated on high-quality AlN templates with an engineerable in-plane lattice constant. The controllability of the in-plane strain originated from the vacancy formation in Si-doped AlN (AlN:Si) and their interaction with edge dislocations. The strain state of the Si:AlN top interface could be well depicted by a dislocation-tilt model depending on the buffer strain state, threading dislocation density (TDD), and regrown Si:AlN thickness. The validity of the model was verified by cross-sectional TEM analysis. With a gradually widened lattice constant of regrown Si:AlN layer, strain-induced defects of subsequently grown n-AlGaN was suppressed. Therefore, growing a current spreading layer which possesses a moderate Al content (<65%), decent thickness (>1.5 µm), and a low TDD (<1.0 × 10 9 cm −2 ) simultaneously becomes possible. Additionally, the idea of an optimal edge TDD ( ρ e, o p t ) in the AlN buffer was revealed for growing high-quality n-AlGaN layers with a targeted thickness. After a deliberate strain-TDD engineering for Si:AlN and n-AlGaN, high-power UVC LEDs (λ = 275 nm, P > 200 mW) with a low forward voltage (Vf = 5.7 volt) were demonstrated at I = 1.35 A. The low forward voltage under high current injection density was attributed to the success in preparation of a low series resistance and high-quality n-AlGaN current spreading layer. Graphical abstract: Image, graphical abstract